Precancerous cervical lesion screening acceptance among women in Eastern Ethiopia - Endalew G Sendo; Elias Bekele Wakwoya; Chala Gari Sadi (BMJ Open, 2023)
Objective This study assessed perceived barriers, precancerous cervical lesion screening acceptance, and associated factors among women in Eastern Ethiopia.Setting This study was conducted in Hiwot Fana Specialized Hospital and Jugal Hospital.Study design This study is a facility-based cross-sectional study.Study participants This study included 1181 women aged 25–49 years. Bivariate and multivariable logistic regression was used to evaluate the relationship between variables and control confounders.Results Nearly half of the participants (587 or 49.7%) agreed to be screened for precancerous cervical lesions. Seventy-six per cent of those checked were negative for visual inspection with acetic acid, 18.5% were positive, and 5.7% had cancer-like lesions. In multivariable analysis, fear of discomfort from the screening procedure, having a male screener, and embarrassment were the perceived barriers that were inversely associated with screening acceptance.Conclusions The uptake of the screening service in the study area was not satisfactory, indicating that the programme was underutilised in the area.